Surgical Endoscopy: Future Directions - Sippey, Megan; Lam, Wanda; Ali, Ahmed; Marks, Jeffrey (Digestive Disease Interventions, 2018)
Since the introduction of the modern endoscope in 1957, numerous advances have been made in its use. The endoscope has transitioned from a primarily diagnostic tool at its inception, to now offering a plethora of therapeutic interventions including Natural Orifice Transluminal Endoscopic Surgery (NOTES). Advances in the endoscope, endoscopic imaging modalities, and therapeutic tools and platforms have contributed to recent, and upcoming, progression in NOTES. Current states of these advancements are reviewed.
Keywords: Natural Orifice Transluminal Endoscopic Surgery; novel endoscopic technology; robotic endoscopy